The experiences of New Zealand assistant language teachers in Japan : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, New Zealand - Spite, Stephanie Margaret Elizabeth (Massey University, 2016)
The objective of the research was to gain an insight into the work experiences of New Zealand Assistant Language Teachers (ALTs) in Japan. Five previous ALTs who were hired through the Japan Exchange and Teaching Programme (JET) were interviewed on their experiences living in Japan and working in Japanese schools. I also provide insights from my own experiences as an ALT. Interviews were analyzed and recurring or major themes were identified; strengthened identities as New Zealanders, shared value with Māori in Japanese culture, very little conflict, different cultural acceptance of working many hours overtime and avoidance of conflict through being indirect, and the ALT being a native speaker celebrity and a joker/entertainer. The research has implications for future ALTs to be more informed and prepared for what they might encounter on the job, and for Japanese teachers to gain an insight into some New Zealand ALT perspectives, which may be illuminating for those who may not have been previously exposed to New Zealand culture.
Keywords: Teachers' assistants; Language teaching assistants; Teachers, Foreign; Employment; Social aspects; Japan; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education